Experiment and simulation on NMR and electrical measurements on Liège Chalk - Li, Liangmou; Shikhov, Igor; Zheng, Yong; Arns, Christoph Hermann (Diffusion Fundamentals, 2014)
Liège Chalk is a limestone of considerable commercial interest to the petroleum industry and formation factor a quantity required in this context. In this work we compare the formation factors based on electrical conductivity and diffusional displacement in a long time limit both experimentally and numerically. Measurements are performed on Liège Chalk samples while simulations are performed on two model structures represented by randomly packed ellipsoids and utilizing a Gaussian random field approach. We ensure similarity in petrophysical sense of modelled media to Liège Chalk by matching experimental and simulated NMR relaxation response, Mercury Injection Capillary Pressure curves and electrical resistivity. Following this, the diffusional-based formation factor is estimated from a set of apparent diffusion coefficients in the tortuosity limit obtained with PGSTE NMR. All measurements have been numerically-simulated and are in good agreement with experiment. We have shown that for Liège Chalk, the NMR diffusion and electrical resistivity based formation factors do agree.